Government Fiscal Policies and Redistribution in Asian Countries - Iris Claus; Jorge Martinez-Vazquez; Violeta Vulovic (Asian Development Bank (ADB), 2012)
This paper assesses the impact of government fiscal policies on income inequality in Asia. It discusses the role and effectiveness of redistributive fiscal policies and quantifies the effects of taxation and government expenditure on income distributions. Panel estimation for 150 countries with data between 1970 and 2009 confirms international empirical findings for Asia. Tax systems tend to be progressive but government expenditures are a more effective tool for redistributing income. Moreover, the results suggest some distinctive differential distributive effect for government expenditure on social protection in Asia. Social protection spending appears to increase income inequality, whereas it reduces it in the rest of the world. Also, adversely affecting the distribution of income in Asia is government expenditure on housing. Some options for improving the effectiveness of fiscal policies in Asia are discussed.
hdl:11540/4230
Keywords: 330; Finanzpolitik; Umverteilung; Einkommensverteilung; Asien